Study Of Clinical Profile of Allergic Contact Dermatitis In Pune - Sayal S K; Das A L; Kumar Ashok (Wolters Kluwer Medknow Publications, 1999)
One hundred and twenty five cases of clinically diagnosed allergic contact dermatitis were studied. All patients were subjected to patch test with standard test allergens and also with suspected test allergens based on history and clinical profile. Allergic contact dermatitis due to Parthenium hysterophorus was commonest and found in 64% cases, followed by wearing apparel and jewellery in 16.8%, topical medicaments in 8% and cosmetics and occupational contactants in 5.6% cases each. The common individual allergens other than parthenium, were nickel in 8.8%, leather, hair dye and cement in 3.2% each, nitrofurazone and petrol, oil, lubricant (POL) in 2.4% each. Patch test with suspected allergens was positive in 72% of cases.